2021
DOI: 10.1093/pm/pnaa463
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Pain Hypersensitivity and Lumbopelvic Impairments in Women Diagnosed with Endometriosis

Abstract: Objective To explore hypersensitivity to pain and musculoskeletal impairments in the lumbopelvic area in women with and without endometriosis. Methods This cross-sectional study included 66 women (41 women with endometriosis and 25 healthy women). Pain and related catastrophizing thoughts were assessed through a numeric rating scale, pressure pain thresholds (PPTs), the slump test, and the Pain Catastrophizing Scale. Lumbopel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, this is, to our knowledge, the first randomized controlled trial specifically designed to explore the contribution of a supervised tailored program of therapeutic exercise with special emphasis on the lumbopelvic area on physical and occupational impairments, as well as on the HRQoL of women with endometriosis and a clinical history of symptoms. In this regard, it is acknowledged that, apart from a neuromuscular control of lumbopelvic stability (i.e., a sensory input that alerts the central nervous system about interaction between the body and the environment, providing constant feedback and allowing refinement of movement), deep abdominal muscles (specifically TrA) and lumbar multifidus, whose thicknesses and strengths were found to be reduced in women with endometriosis [18,44], are the main muscles responsible for lumbopelvic stability [89]. Moreover, it has been reported that TrA and the lumbar multifidus are recruited prior shoulder and leg movements in healthy people (30 and 110 ms, respectively) [90,91].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this is, to our knowledge, the first randomized controlled trial specifically designed to explore the contribution of a supervised tailored program of therapeutic exercise with special emphasis on the lumbopelvic area on physical and occupational impairments, as well as on the HRQoL of women with endometriosis and a clinical history of symptoms. In this regard, it is acknowledged that, apart from a neuromuscular control of lumbopelvic stability (i.e., a sensory input that alerts the central nervous system about interaction between the body and the environment, providing constant feedback and allowing refinement of movement), deep abdominal muscles (specifically TrA) and lumbar multifidus, whose thicknesses and strengths were found to be reduced in women with endometriosis [18,44], are the main muscles responsible for lumbopelvic stability [89]. Moreover, it has been reported that TrA and the lumbar multifidus are recruited prior shoulder and leg movements in healthy people (30 and 110 ms, respectively) [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a case-control study focused on visceral osteopathy [37], a retrospective study evaluating electrical muscle stimulation [38] and two randomized controlled trials exploring the potential benefits of pulsed high-intensity laser therapy [39] and yoga [40] have reported a significant improvement in HRQoL in these patients, although the contribution to individ-ual occupational roles have not been addressed yet. Moreover, in contrast to osteopathy (with limited scientific evidence) or laser therapy (with non-standardized dosimetry), therapeutic exercise has been widely demonstrated to induce either soft tissue remodelling [41] and modifications in the nervous system [42], of particular interest in endometriosis given the elevated prevalence of central sensitization in these patients [43,44]. Additionally, it has been shown that regular physical exercise also exerts a protective effect against diseases that involve oxidative and/or inflammatory processes since it induces an increase in the systemic levels of mediators with anti-oxidant and anti-inflammatory properties [45].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as a chronic pain condition, women with endometriosis may have decreased physical activity and experience physical deconditioning, which, in turn, may cause musculoskeletal consequences. Indeed, a poorer physical status, such as lower lumbopelvic mobility and increased fatigue, have been found in women with endometriosis when compared with healthy women [12], which may negatively impact their daily living activities.…”
Section: Introductionmentioning
confidence: 99%